MILK Symposium review: Community-tailored training to improve the knowledge, attitudes, and practices of women regarding hygienic milk production and handling in Borana pastoral area of southern Ethiopia - Amenu, K.; Agga, G.E.; Kumbe, A.; Shibiru, A.; Desta, Hiwot; Tiki, W.; Dego, O.K.; Wieland, Barbara; Grace, Delia; Alonso, Silvia (American Dairy Science Association, 2020)
Milk and milk products are essential in the diets of the Borana pastoral community in Ethiopia. Traditional handling and processing of dairy products using basic equipment and infrastructure coupled with a preference for raw milk consumption pose potential health risks to consumers. We tested the effect of an intervention designed to improve the hygienic handling and safe consumption of milk on the knowledge, attitudes, and practices (KAP) of women who produce and sell dairy products. The intervention consisted of 16 h of training on good milk production practices and prevention of milk-borne diseases. A total of 120 women were trained and their KAP assessed at baseline (pretraining), immediately after training, and 6 mo after training. Overall, training increased the knowledge score of the participants from 75.6 to 91.4% in the immediate post-training assessment, and to 90.0% at 6 mo post-training. Compared with pretraining (58.8%), we found a statistically significant difference in the overall attitude score at the immediate post-training evaluation (64.7%) but not 6 mo after (61.4%). We observed a similar increase in the understanding of correct practices from 49.5% at pretraining to 64.7% 6 mo following the training. For some desirable attitudes and practices, the proportion of women reporting adoption at pretraining was low and the change derived from training still left one-third of respondents displaying a negative attitude and a quarter of them reporting wrong practices. We recommend that future training interventions be complemented with locally adaptable technologies, provision of incentives, and creation of an enabling environment including improved access to clean water and sanitation facilities to affect not only knowledge, but also attitudes and ultimately practices in the long term.